Improving Physical Fitness Of School Students Based On Extracurricular Physical Education Activities - Sultanova Nargizaxon Yakubjanovna (Researchparks Publishing, 2026)
This article examines the pedagogical and psychological significance of extracurricular physical education activities in improving the physical condition of school students. In the context of modern education, reduced physical activity, sedentary lifestyles, and excessive use of digital technologies have a negative impact on students’ health and overall development. Therefore, the effective organization of extracurricular physical education has become an important educational task. The study analyzes the role of sports clubs, physical exercises, active games, and health-oriented activities in developing students’ endurance, strength, coordination, and overall physical fitness. The findings indicate that regular participation in extracurricular physical education activities positively influences not only physical indicators but also students’ motivation, emotional well-being, and social adaptation. Moreover, such activities contribute to the formation of healthy lifestyle habits and increase students’ interest in physical activity. The results of the research demonstrate that extracurricular physical education serves as an effective means of enhancing students’ physical condition and promoting holistic development. The conclusions may be useful for educators and specialists in improving physical education programs within secondary school settings.